(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2015)
This paper discusses two Thai short stories. The first short story is entitled "Maew Haeng Bukit Krueso" (Cat Hill Krueso) by Kanokpong Songsompant. The second short story is "Chon Saeng Tawan" (The Sun shine) by Narongrit Sagdaronnarong. Both of these stories have similarities in terms of theme and character. The theme of both stories is the violence as a result of conflict in the Malay-Muslim community dominated area of southern Thailand. Both stories featured Abdulkadir as the main character. While sharing the same theme and character, both stories are dealt with in different ways and have a different tone. Significant differences were found in terms of the character presented by both short story writers. This paper analyses the character of Abdulkadir in both short stories. Keywords: Pattani Malays, southern Thailand, conflict, violence, Abdulkadir, comparative study